CYTOTOXIC EFFECTS OF JORDANIAN SIMMONDSIA CHINENSIS (LINK) C.K. SCHNEID ON DIFFERENT CANCER CELL LINES - AL-Qizwini, Hani; AL-Khateeb, Ekbal; Mhaidat, Nizar M.; Saleem, Ahmed (European Scientific Journal, ESJ, 2014)
Context: Different parts of Jojoba (Simmondsia chinensis (Link) C.K. Schneid) from the family Simmondsiaceae have been traditionally used in folklore-medicine for skin disorders, wound healing, tumors and many other uses. Objective: The aim was to examine the effect of the total extracts of Jojoba leaves (male & female), testa, seeds and oil on the growth of various cancer cell lines. Materials and methods: Plant parts were subjected for hot extraction by solvents of different polarity (hexane, methanol and ethanol), in addition to cold pressing extraction of seed. Furthermore, the active compounds were isolated by preparative thin layer chromatography, followed by identification with chemical reagents along with various methods of chromatography and spectral analysis for simmondsin and three of its derivatives namely Simmondsin-3’-ferulate,4,5-Didemethylsimmondsin and 4- Demethylsimmondsin -2’- ferulate. In addition, phenolic compounds, phytosterols, toccopherols and fatty acids were also identified by the same methods. The evaluation of the acute cytotoxic effect of the extracts on human cancer cell lines using human melanoma (MV 3), breast (MCF 7), and colorectal (HCT 116) tumor cell lines, was determined using 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results: According the IC50 values, both jojoba oil (hexane extract & cold pressing extract) and methanolic extract of testa have antitumor activity, more potent than the other parts, against HCT 116, MV 3 cancer cells. Moreover, Jojoba extracts induced a dose-dependent cytotoxicity. Discussion and conclusion: Plant extracts induced variable degrees of cytotoxicity against cancer cell lines due to their active constituents which were observed in different parts of the plant.